KOMPLEKSITAS DAERAH, PENGAWASAN INTERNAL DAN DAMPAKNYA TERHADAP KETEPATWAKTUAN PELAPORAN KEUANGAN PADA PEMERINTAH DAERAH DI INDONESIA - Muhtar, Muhtar (Jurnal Manajemen, 2022)
This study aims to examine the effect of the complexity of local government and local government internal control on the timeliness of local government financial reporting in Indonesia. This study produces panel data with a total of 1524 observations from 508 local governments in Indonesia. Data analysis was performed by panel data regression. This study found that there were still local governments in Indonesia during the 2016-2018 period that had not been able to submit their financial reports on time with an average delay of 2 days from the specified reporting deadline. Furthermore, the empirical findings of this study reveal that the complexity of local government does not affect the timeliness of local government financial reporting, while internal control shows a positive influence. This study also recommends local governments to continuously improve the quality of internal control to be more effective and efficient in order to oversee the local government financial reporting process so that it can be completed on time.